High contrast yellow mosaic patterns are prey attractants for orb‐weaving spiders. (11th February 2020) - Peng, Po; Stuart‐Fox, Devi; Chen, Szu‐Wei; Tan, Eunice J.; Kuo, Guan‐Lin; Blamires, Sean J.; Tso, I‐Min; Elgar, Mark A.
Abstract: Many animals improve their foraging success by producing signals that exploit the sensory biases of potential prey, but the specific properties that make these sensory traps effective remain unclear. We combine field experiments with phylogenetic comparative analyses to investigate the visual luring properties of different signal designs in web‐building spiders. Our field experiments used cardboard spider models to examine the effects of area of colour patches, colour and pattern on the foraging success of the colourful giant wood spider, Nephila pilipes . These experiments revealed that both the colour (yellow) and pattern (yellow and black mosaic) are essential for luring prey in a high ambient light environment. We subsequently used phylogenetic comparative analyses to demonstrate an evolutionary association between prey viewing environment and spider ventral signal among 63 species of orb‐weavers from 53 genera. Combined, our data show that (a) the colour of the bright body parts of orb‐weavers is essential for both diurnal and nocturnal prey attraction, whereas the pattern and area of colour patches are important for diurnal foraging and (b) the evolution of these visual lures is associated with the viewing environment, specifically ambient light intensity. We conclude that the effectiveness of colour luring might be a major driver of the convergent evolution of yellow mosaic patterns in phylogenetically divergent orb‐weavers. Our discoveries indicate that prey colour preferences and signal efficacy play a significant role in the evolution of visually mediated prey‐luring systems. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article. 摘要: 許多動物可藉由體色傳遞誘引訊號, 利用獵物的感官偏好, 增加自身的捕食成功率。然而, 是哪些具體特質使此一欺騙訊號得以有效, 至今尚未明瞭。 本研究結合田野實驗與親緣比較方法, 探討結網性蜘蛛的視覺誘引特徵。在田野實驗中, 我們製作人面蜘蛛的色紙模型, 探討色斑的面積, 和顏色與排列形式, 對捕食成功率的影響。結果顯示, 在高光源環境下, 訊號的顏色 (黃色), 和排列形式 (黃色與黑色交錯之斑紋), 是誘引昆蟲獵物的關鍵因子。 使用親緣比較方法, 我們分析53屬63種結網性蜘蛛的自然史資料, 證實蜘蛛腹部體色的演化, 與獵物視覺環境相關。 整合田野實驗與親緣比較方法之結果, 我們得知 (一) 結網性蜘蛛體表斑紋的顏色, 為誘引日行和夜行性獵物的必要因素, 而排列形式和面積對於日間捕食活動極其重要； (二) 黃色與黑色交錯之斑紋, 此項表徵能有效誘引昆蟲, 且其演化歷程與視覺環境相關, 尤其是環境光源強度。 我們推論, 誘引獵物之效果, 是驅使親緣關係歧異的結網性蜘蛛, 演化出黃色與黑色交錯斑紋的主要因子。 我們的研究結果指出, 獵物的視覺偏好和誘引獵物之功效, 在欺騙訊號的演化中扮演重要角色。